The commodities supercycle's end and political risk. Issue 2 (7th February 2016) - Unknown
Abstract : The commodities supercycle has ended, and commodity prices have dropped steeply. This has strained the economies of net commodity exporters, most of which are emerging-market and developing countries. Substantial reductions in export revenues have prompted budget cuts and other drastic remedial action that have in many cases reduced government assistance to general populations and produced shortages of basic goods and services. As a result, popular discontent and instability have broadly increased political risk.